The Effect of Personal Guidance on the Formation of Child Spiritual Intelligence - Utomo, Prio (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2022)
Personal guidance is a guidance given by an expert to individuals or groups, in helping individuals face and solve personal problems. The research method used in this research is descriptive quantitative research method. The results of this study are that there is a moderate relationship between the correlation of the implementation of personal guidance and the formation of children's spiritual intelligence. The link between the indicators of the invitation to pray in congregation with formation.